High-entropy alloy 3D aerogel for seawater desalination and preparation method thereof

Through the preparation of high-entropy alloy 3D aerogel, the sol-gel method and directional freezing technology are used to solve the problems of high equipment costs, large energy consumption and low thermal efficiency in seawater desalination technology, and efficient and stable seawater evaporation is achieved, which meets the needs of the Desalination needs and demonstrate low-cost, environmentally friendly solutions.

CN119193113APending Publication Date: 2024-12-27YANCHENG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411278530.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing seawater desalination technology has problems such as high equipment costs, high energy consumption, difficulty in maintenance, low thermal efficiency and poor material stability of traditional solar evaporators, which limits its performance in practical applications.

Method used

Using high-entropy alloy 3D aerogel through sol-gel method and directional freezing technology, using chitosan, high-entropy alloy powder and acetic acid as raw materials, aerogel with porous structure and excellent photothermal conversion performance was prepared, combined with a broadband Gap and narrow bandgap elements improve the photothermal conversion efficiency and carry out seawater evaporation through solar energy.

Benefits of technology

It has achieved low-cost, low-energy consumption and stable seawater desalination, improved the photothermal conversion efficiency and evaporation rate, met the needs of seawater desalination, and the materials can be adjusted and environmentally friendly, and has industrialization potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193113A_ABST
    Figure CN119193113A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy alloy 3D aerogel for sea water desalination and a preparation method thereof, and belongs to the technical field of composite material synthesis. Chitosan, high-entropy alloy powder FeCoNiCrAl and acetic acid are used as raw materials and reagents, the chitosan and the high-entropy alloy powder (FeCoNiCrAl) are mixed and weighed according to a certain proportion through a sol-gel method, and are mixed and stirred at a certain temperature to prepare the high-entropy alloy 3D aerogel for sea water desalination. The preparation method comprises the following steps: mixing the raw materials, freeze-drying to prepare a precursor of the aerogel, curing the precursor through a NaOH solution, washing with deionized water, and freeze-drying to obtain the high-entropy alloy 3D aerogel. According to the prepared high-entropy alloy 3D aerogel, the photo-thermal conversion efficiency can be greatly improved, and the evaporation rate of seawater is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material synthesis, and particularly relates to a high entropy alloy 3D aerogel for seawater desalination and a preparation method thereof. Background Art

[0002] With the growth of global population and economic development, the problem of water shortage is becoming increasingly serious. According to statistics, about 3 billion people in the world are facing the problem of water shortage. In order to solve this problem, seawater desalination has become an important research direction. At present, seawater desalination technologies mainly include reverse osmosis, multi-effect evaporation, electrodialysis, etc., but these technologies have problems such as high equipment cost, high energy consumption, and difficult maintenance.

[0003] As a clean and renewable energy source, solar energy has great potential in the field of seawater desalination. A solar evaporator is a device that uses solar energy to evaporate seawater to achieve seawater desalination. However, traditional solar evaporators have problems such as low thermal efficiency and poor material stability, which limit their performance in practical applications. Therefore, studying an efficient and stable solar evaporator material is of great significance to promote the development of seawater desalination technology.

[0004] As a new type of material, high entropy alloy has excellent mechanical properties, corrosion resistance, thermal stability and adjustable optical properties. Due to these unique properties, high entropy alloys have shown great application potential in many fields, including aerospace, energy conversion, biomedicine, electronic devices and marine engineering. In recent years, the application of high entropy alloys in the energy field has received widespread attention. Studies have found that high entropy alloys have high photothermal conversion efficiency and can effectively absorb sunlight and convert it into thermal energy. Therefore, there is great potential in using high entropy alloys to construct solar evaporators. Summary of the invention

[0005] Purpose of the invention: In view of the problems of low efficiency, high energy consumption and high cost of seawater desalination technology, the present invention provides a high entropy alloy 3D aerogel for seawater desalination and a preparation method thereof. Chitosan, high entropy alloy powder (FeCoNiCrAl) and acetic acid are used as raw materials and reagents, and chitosan and high entropy alloy powder (FeCoNiCrAl) are weighed and mixed in a certain proportion by a sol-gel method, mixed and stirred at a certain temperature, and freeze-dried to prepare a precursor of aerogel. Subsequently, the precursor is solidified by a NaOH solution, washed with deionized water, and then freeze-dried to obtain a 3D aerogel.

[0006] The present invention provides a method for preparing a high entropy alloy 3D aerogel for seawater desalination, comprising the following steps:

[0007] Step 1, dissolving chitosan in acetic acid solution, and stirring evenly to obtain a mixed solution;

[0008] Step 2: adding high entropy alloy powder FeCoNiCrAl into the mixed solution obtained in step 1, and stirring continuously;

[0009] Step 3, freeze-drying the mixed solution obtained in step 2 to obtain an aerogel precursor, then immersing the aerogel precursor in a NaOH solution for solidification, and washing with deionized water until neutral;

[0010] Step 4: Dry the precursor obtained in step 3 by freeze drying to obtain high entropy alloy 3D aerogel.

[0011] Furthermore, in step 1, the volume fraction of acetic acid in the acetic acid solution is 1% to 5%; the solid-liquid ratio of chitosan to the acetic acid solution is (3 to 10) g: (100 to 500) mL.

[0012] Furthermore, the stirring method in step 1 is: heating and stirring with a temperature magnetic stirrer, the temperature is set at 60-80° C., and the speed is set at 200-400 r / min.

[0013] Furthermore, in step 2, the mass ratio of chitosan to high entropy alloy powder FeCoNiCrAl is (3-10): (1-10).

[0014] Furthermore, the stirring method in step 2 is: the stirring temperature is set to 60-80° C., the stirring time is 60-180 min, and the rotation speed is set to 200-400 r / min.

[0015] Furthermore, in step three, the freeze-drying time is 24 to 48 hours, and the freeze-drying temperature is -50 to -80°C.

[0016] Furthermore, in step three, the concentration of the NaOH solution is 2 to 5 mol / L.

[0017] Furthermore, in step 4, the freezing temperature is -50 to -80°C, and the freezing time is 24 to 96 hours.

[0018] Beneficial effects: Based on the sol-gel method and directional freezing technology, the present invention uses low-cost chitosan and high entropy alloy as raw materials, and prepares 3D porous aerogels with seawater desalination function through structural design. The internal porous three-dimensional structure can effectively reduce the scattering of sunlight inside the material, further improving the photothermal conversion efficiency of the aerogel. In addition, the high entropy alloy itself can combine wide bandgap and narrow bandgap elements, so that the alloy has a good absorption effect on visible light to near-infrared light in the solar spectrum, and a large lattice distortion will be generated inside the high entropy alloy. This distortion can increase the scattering and absorption of light inside the material, which is beneficial to improve the photothermal conversion efficiency. Therefore, the photothermal conversion efficiency can be greatly improved and the evaporation rate of seawater can be accelerated.

[0019] The high entropy alloy 3D aerogel prepared by the present invention has strong structural design and excellent photothermal conversion performance, which can fully meet the requirements of seawater desalination. The directional freezing technology used in the invention can design the appearance structure of the aerogel according to molds with different structures. At the same time, the material prepared by this technology has a uniform internal pore structure. The controllability of this microscopic and macroscopic structure (the structural morphology of the aerogel can be controlled by controlling the freezing speed and the growth direction of ice crystals) can not only expand the contact area between the aerogel and sunlight, but also effectively reduce the scattering of light inside it.

[0020] The high entropy alloy 3D aerogel prepared by the present invention has a wide range of raw materials and low prices, a simple preparation process, and low equipment costs. The chitosan, high entropy alloy, acetic acid and NaOH solution used in the present invention are all commonly used materials and reagents in industry, and are relatively low in price. The magnetic stirrer and freeze dryer used are both common equipment, and are easy to achieve scale and industrialization.

[0021] The high entropy alloy 3D aerogel prepared by the present invention uses solar energy as a power source, does not require energy costs, and is green and environmentally friendly. Solar energy is an inexhaustible renewable energy source on the earth. The 3D aerogel prepared by the present invention for seawater desalination only needs to convert solar energy into thermal energy through photothermal materials, locally heat the seawater, generate high temperature to evaporate the seawater, and then condense and collect the evaporated water vapor to obtain fresh water that can be used for daily life. No energy consumption costs are generated in this process. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a SEM image of the high entropy alloy powder FeCoNiCrAl and the prepared 3D aerogel in Example 1 of the present invention;

[0023] Figure 2 This is a real experiment diagram of the 3D aerogel prepared in Example 2 of the present invention being applied to seawater desalination;

[0024] Figure 3The 3D aerogel prepared in Example 2 of the present invention is used for the change of ion concentration in seawater before and after evaporation for seawater desalination. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0026] In the following examples, chitosan was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., and high entropy alloy powder FeCoNiCrAl was purchased from MCC Research New Materials Co., Ltd.

[0027] Example 1

[0028] Step (1), weigh 3 g of chitosan using an electronic balance, dissolve it in 100 mL of acetic acid solution (the volume fraction of acetic acid is 1%), and heat and stir using a temperature magnetic stirrer: place the mixture at 80° C. under vigorous stirring for 30 minutes, and set the rotation speed to 400 r / min.

[0029] Step (2), then weigh 6 g of high entropy alloy powder FeCoNiCrAl and add it to the mixed solution in step (1), and stir continuously at 80° C. for 1 hour with the rotation speed set to 300 r / min until it becomes a uniformly mixed solution.

[0030] Step (3), placing the solution obtained in step (2) in a freeze dryer for freeze drying for 48 hours, then immersing the dried solid sample in 100 mL of NaOH solution (2M) to solidify, and washing with deionized water until neutral.

[0031] Step (4), finally drying the sample obtained in step (3) at -60°C by a freeze dryer for 48 hours, and the final sample obtained is FeCoNiCrAl-based 3D aerogel.

[0032] Step (5), placing an evaporating dish in a flat-bottomed container, taking an appropriate amount of seawater and pouring it into the evaporating dish, spreading the aerogel prepared in step (4) on the evaporating dish to cover the seawater, and then placing a beaker upside down on the evaporating dish to evaporate, and the generated water vapor hits the wall of the beaker, cools and falls to obtain fresh water, thereby achieving the separation of seawater from salt water.

[0033] Example 2

[0034] A high entropy alloy 3D aerogel for seawater desalination and a preparation method thereof, the specific steps are as follows:

[0035] Step (1), weigh 3 g of chitosan using an electronic balance, dissolve it in 100 mL of acetic acid solution (the volume fraction of acetic acid is 2%), and heat and stir using a temperature magnetic stirrer: place the mixture at 80° C. under vigorous stirring for 30 minutes, and set the rotation speed to 400 r / min.

[0036] Step (2), then weigh 5 g of high entropy alloy powder FeCoNiCrAl and add it to the mixed solution in step (1), and stir continuously at 80° C. for 1 hour with the rotation speed set to 300 r / min until it becomes a uniformly mixed solution.

[0037] Step (3), placing the solution obtained in step (2) in a freeze dryer for freeze drying for 48 hours at a freeze drying temperature of -50°C, then immersing the dried solid sample in 100 mL of NaOH solution (2M) to solidify, and washing with deionized water until neutral.

[0038] Step (4), finally drying the sample obtained in step (3) at -60°C by a freeze dryer for 48 hours, and the final sample obtained is FeCoNiCrAl-based 3D aerogel.

[0039] Step (5), placing an evaporating dish in a flat-bottomed container, taking an appropriate amount of seawater and pouring it into the evaporating dish, spreading the aerogel prepared in step (4) on the evaporating dish to cover the seawater, and then placing a beaker upside down on the evaporating dish to evaporate, and the generated water vapor hits the wall of the beaker, cools and falls to obtain fresh water, thereby achieving the separation of seawater from salt water.

[0040] Example 3

[0041] A high entropy alloy 3D aerogel for seawater desalination and a preparation method thereof, the specific steps are as follows:

[0042] Step (1), weigh 2 g of chitosan using an electronic balance, dissolve it in 100 mL of acetic acid solution (the volume fraction of acetic acid is 2%), and heat and stir using a temperature magnetic stirrer: place the mixture at 80° C. under vigorous stirring for 30 minutes, and set the rotation speed to 400 r / min.

[0043] Step (2), then weigh 4 g of high entropy alloy powder FeCoNiCrAl and add it to the mixed solution in step (1), and stir continuously at 80° C. for 1 hour with the rotation speed set to 400 r / min until it becomes a uniformly mixed solution.

[0044] Step (3), placing the solution obtained in step (2) in a freeze dryer for freeze drying for 48 hours, then immersing the dried solid sample in 100 mL of NaOH solution (1 M) to solidify, and washing with deionized water until neutral.

[0045] Step (4), finally drying the sample obtained in step (3) at -80°C by a freeze dryer for 24 hours, and the final sample obtained is FeCoNiCrAl-based 3D aerogel.

[0046] Step (5), placing an evaporating dish in a flat-bottomed container, taking an appropriate amount of seawater and pouring it into the evaporating dish, spreading the aerogel prepared in step (4) on the evaporating dish to cover the seawater, and then placing a beaker upside down on the evaporating dish to evaporate, and the generated water vapor hits the wall of the beaker, cools and falls to obtain fresh water, thereby achieving the separation of seawater from salt water.

[0047] The SEM images of the high entropy alloy powder FeCoNiCrAl and the prepared 3D aerogel in Example 1 of the present invention are as follows: Figure 1 As shown, a and b are SEM images of high entropy alloy powder FeCoNiCrAl, and c and d are SEM images of 3D aerogel prepared in Example 1. The 3D aerogel prepared in Example 2 is applied to the actual experiment of seawater desalination. Figure 2 As shown; the change of ion concentration in seawater before and after evaporation in Example 2 is as shown Figure 3 As shown in the results, the 3D aerogel prepared by the present invention has good stability against three representative ions K in seawater. + , Na + ,Mg 2+ The removal rate is significant, meeting the standards of the World Health Organization (WHO) and the U.S. Environmental Protection Agency (EPA).

[0048] The present invention uses high entropy alloy powder (FeCoNiCrAl) and chitosan as raw materials, and adopts sol-gel method and directional freezing technology to prepare high entropy alloy 3D aerogel. Then, the evaporation performance of aerogel in pure water and seawater is tested, and it is found that the evaporation rate of aerogel in pure water is as high as 4.35 kg m -2 h -1 The evaporation rate in seawater is slightly reduced, but it has good durability. The 3D aerogel prepared by the present invention acts on real seawater, and the ion content of seawater before and after evaporation is tested. The results show that the aerogel has good ion resistance to three representative ions in seawater, K+, Na+, and Mg 2+ The removal rate is significant, meeting the standards of the World Health Organization (WHO) and the U.S. Environmental Protection Agency (EPA).

[0049] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention.

Claims

1. A method for preparing high entropy alloy 3D aerogel for seawater desalination, characterized in that: The following steps are involved: Step 1, dissolving chitosan in acetic acid solution, and stirring evenly to obtain a mixed solution; Step 2: adding high entropy alloy powder FeCoNiCrAl into the mixed solution obtained in step 1, and stirring continuously; Step 3, freeze-drying the mixed solution obtained in step 2 to obtain an aerogel precursor, then immersing the aerogel precursor in a NaOH solution for solidification, and washing with deionized water until neutral; Step 4: Dry the precursor obtained in step 3 by freeze drying to obtain high entropy alloy 3D aerogel.

2. The preparation method according to claim 1, characterized in that: In the step 1, the volume fraction of acetic acid in the acetic acid solution is 1% to 5%; the solid-liquid ratio of chitosan to the acetic acid solution is (3 to 10) g: (100 to 500) mL.

3. The preparation method according to claim 1, characterized in that: The stirring method in step 1 is: heating and stirring with a temperature magnetic stirrer, the temperature is set at 60-80° C., and the speed is set at 200-400 r / min.

4. The preparation method according to claim 1, characterized in that: In the step 2, the mass ratio of chitosan to high entropy alloy powder FeCoNiCrAl is (3-10): (1-10).

5. The preparation method according to claim 1, characterized in that: The stirring method in step 2 is: the temperature during stirring is set at 60-80° C., the stirring time is 60-180 min, and the rotation speed is set at 200-400 r / min.

6. The preparation method according to claim 1, characterized in that: In the step 3, the freeze-drying time is 24 to 48 hours, and the freeze-drying temperature is -50 to -80°C.

7. The preparation method according to claim 1, characterized in that: In the step 3, the concentration of the NaOH solution is 2-5 mol / L.

8. The preparation method according to claim 1, characterized in that: In the step 4, the freezing temperature is -50 to -80°C, and the freezing time is 24 to 96 hours.

9. A high entropy alloy 3D aerogel prepared according to the preparation method according to any one of claims 1 to 8.